Scratch hardness of rare-earth substituted calcium aluminosilicate glasses - She, Jiangbo; Sawamura, Shigeki; Wondraczek, Lothar (Journal of Non-Crystalline Solids: X, 2019)
We report lateral deformation experiments on rare earth substituted glasses from percalcic CaO-Al 2 O 3 -SiO 2 -Tm 2 O 3 . Using instrumented Berkovich indentation with normal loads below 100 mN, the scratch hardness was obtained from the work of lateral deformation per deformed volume in the elastic-plastic regime. The positive effect of rare-earth substitution on normal hardness, Poisson's ratio and Young's modulus was found to extent also to scratch hardness: in 25CaO-15Al 2 O 3 -60SiO 2 , partial replacement of alumina by Tm 2 O 3 leads to an enhancement of the scratch hardness by about 1 GPa per 2 mol% of substitution, reaching the highest values of scratch hardness which have been reported for oxide glasses thus far. The enhancement of scratch hardness is attributed to enhanced cation packing fraction and super-structural cohesion as a result of rare earth substitution. The previously reported linear correlation between scratch hardness and bulk modulus is confirmed.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Calcium aluminosilicate; CAS; Glass; Hardness; Rare earth; Scratch